The use of information and communication technologies as a strategy to reduce fruit and vegetable waste - Muñiz-López, Héctor Simón (Universidad Autónoma de Tamaulipas, 2021)
The waste of fruits, vegetables and other foods is a global problem, which can be reduced with the use of Information and Communication Technologies (ICTs) in all scenarios of food systems. The purpose of this work was to identify how some ICTs that have been proposed and implemented in electronic commerce intervene in different food chains where they have been applied as strategies to reduce the waste of fruits and vegetables. Features of some technologies are shown: Internet of Things (IoT), RFID sensors, crowdsourcing, mobile applications (APPs), web platforms and cloud computing technology. Technological tools provide valuable information for analysis and applications by stakeholders to make the best decisions and better contribute to reducing food waste and responding to timely actions that promote food and nutritional security and caring for the environment. ICTs can serve as guidelines for the different actors involved in sustainable food systems. They can also be implemented in electronic commerce in Mexico, in a way of obtaining economic, social and environmental benefits.